Classroom opportunities that foster willingness to communicate - Tiu, Glendora V. (Animo Repository, 2011)
This study sought to analyze the classroom opportunities provided by Chiang Kai Shek College (CKSC) to the first year high school students in relation to the latter"s willingness to communicate (WTC). It employed the descriptive research design to find out what these opportunities are. Likewise, it examined if these opportunities can provoke in the students the desire to communicate, as well as the manner by which students react and respond to the opportunities given them. Data were gathered from 320 first year students through the use of the researcher-made questionnaire/checklist. Informal interviews and observations were also done to enrich the study. Findings showed that all the opportunities provided by the school were intended to move students to speak; however, not all opportunities were found to provoke in the students the desire to communicate orally in the target language. It was also discovered that practical speaking or a normal conversation was one of the best opportunities the language students could experience inside and outside the classroom. Furthermore, the study showed that ordinary speech, talk or dialog is of big assistance to a language learner in the context of confidence, fluency, and competence. The researcher concluded that one"s WTC is not solely dependent on the students" attitude and motivation, but also on the opportunities provided them and the manner by which these opportunities are administered.